Analysing the impacts of air quality policies on ecosystem services; a case study for Telemark, Norway. (15th January 2018) - Hein, L.; White, L.; Miles, A.; Roberts, P.
Abstract: There is an increasing interest in considering the effects of air pollution on ecosystem services supply in order to enhance cost-benefit analyses of air pollution policies. This paper presents a generic, conceptual approach that can be used to link atmospheric deposition of air pollutants to ecosystem services supply and societal benefits. The approach is applied in a case study in the Telemark county of Norway. First, we examine the potential effects of four European air quality policy scenarios on N deposition in the ecosystems of this county. Second, we analyse the subsequent impacts on the supply of three ecosystem services: carbon sequestration, timber production and biodiversity. Changes in the supply of the first two services are analysed in both physical and monetary units, biodiversity effects are only analysed in physical terms. The scenarios derive from work conducted in the context of the European National Emissions Ceilings Directive. In the 2010 base case the benefits of carbon sequestration are estimated at 13 million euro per year and the value of timber harvesting at 2.9 million euro per year. Under the examined policy scenarios aiming to reduce nitrogen emissions the societal benefits resulting from these two ecosystem services in Telemark are found to be reduced; the scenarios have little effect on terrestrial biodiversity. Such results cannot be scaled up, individual ecosystem services respond differently to changes in air pollution depending upon type of pollutant, type of ecosystem, type of service, and the magnitude of change. The paper further presents an analysis of the uncertainties that need to be considered in linking air pollution and ecosystem services including those in deposition rates, ecosystem responses, human responses and in the values of ecosystem services. Our conceptual approach is also useful for larger scale analysis of air pollution effects on ecosystem services, for example at national or potentially European scale. Highlights: Including ecosystem services in CBA of air quality policies requires a spatial approach. Impacts of air pollution on ecosystem services vary by type of pollutant, service and context. In our case study, N deposition increases the value of timber supply and carbon sequestration. Scenario analyses of air pollution impacts on ecosystem services are prone to considerable uncertainty.